1870
DOI: 10.5962/bhl.title.20559
|View full text |Cite
|
Sign up to set email alerts
|

The strawberry, and its culture: with a descriptive catalogue of all known varieties

Abstract: Nicaise, Admiral Dundas, &c., the ground can hardly be made too deep or too rich. The latter varieties will fail utterly where the Wilson or the Agriculturist would do tolerably well. The President Wilder exhibits in many respects its relationship to La Constante, and, like that fine berry, it is fond of good feeding. While many kinds of strawberries will do well, although poorly fed, there is hardly one that will not do better on well-manured land ; and in general, we may say, as in the case of other crops, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
3

Year Published

1981
1981
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 0 publications
1
23
0
3
Order By: Relevance
“…Sequence analysis of the DNA region downstream of clpC revealed a start codon of a 555 bp ORF (ORF555) located 139 bp downstream of clpC. ORF555 is preceded by a putative RBS and could encode a 21 kDa protein with 45 % identity to the gene product of B. subtilis yvyD (Drzewiecki et al, 1998) and 30-37 % identity to σ&% modulating factors of various Gramnegative bacteria (Merrick & Coppard, 1989). A putative Rho-independent transcription terminator is located 5 nucleotides downstream of the ORF555 stop codon.…”
Section: Sequence Analysis Of the Upstream And Downstream Regions Of mentioning
confidence: 99%
“…Sequence analysis of the DNA region downstream of clpC revealed a start codon of a 555 bp ORF (ORF555) located 139 bp downstream of clpC. ORF555 is preceded by a putative RBS and could encode a 21 kDa protein with 45 % identity to the gene product of B. subtilis yvyD (Drzewiecki et al, 1998) and 30-37 % identity to σ&% modulating factors of various Gramnegative bacteria (Merrick & Coppard, 1989). A putative Rho-independent transcription terminator is located 5 nucleotides downstream of the ORF555 stop codon.…”
Section: Sequence Analysis Of the Upstream And Downstream Regions Of mentioning
confidence: 99%
“…This chiral polymer occurs as spherical hydrophobic granules in the cells of a wide variety of bacteria (5) and is easily harvested by a simple cell rupture (6,7). The solid state structure of this polymer has been studied intensively (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…However, owing to the extreme complexity of the initial stage of degradation, the enzymatic mechanism of poly(3-hydroxybutyrate) digestion in bacterial cells has not been fully clarified yet demonstrated that poly(3-hydroxybutyrate) granules isolated from Bacillus megaterium KM, which did not undergo self-digestion, were hydrolyzed by a depolymerizing enzyme system present in the soluble fraction of poly( 3-hydroxybutyrate)depleted Rhodospirillum rubrum cells, yielding D( -)-3-hydroxybutyrate as a main product and its dimeric ester (DD-dimer) as a minor product [4]. The latter product was further hydrolyzed to the monomer by a hydrolase (hydroxybutyrate-dimer hydrolase) partially purified from R. rubrum.…”
mentioning
confidence: 99%